A stochastic model for operating room unique equipment planning under uncertainty. Issue 3 (2015) - Razmi, J.; Yousefi, M.S.; Barati, M.
Abstract: In the present economic context, the operating theatre is considered as a critical activity in health care management. This paper describes a model for Operating Room (OR) planning under constraint of a unique equipment. At first level we schedule elective surgeries under the uncertainty of using a unique equipment. At the second level we consider emergency surgeries, and at the third level a coefficient factor for surgeons is introduced in using this unique equipment. A new mathematical programming model is first proposed and at the second and third level, a new stochastic mathematical programming model is proposed.Lingo is used as an exact approach, because of NP-hardness a Metaheuristic approach (Differential Evolution (DE)) is proposed for large size problems.